Nervous Shock: Time and Space - Bain, Bernadette (International Journal of Bahamian Studies, 2015)
Liability for psychiatric injury, also known as nervous shock, may pose several challenges when considered as an aspect of personal injury. Within the context of Bahamian tort law, it is an emerging area, which so far has been dealt with only briefly. Several questions arise when assessing nervous shock, such as determining whether a defendant is liable and whether the plaintiff should be awarded damages. In The Bahamas the approach has been similar to that in other jurisdictions such as England and other Commonwealth states. In these jurisdictions the issue has been whether the cause of the psychiatric injury was reasonably foreseeable, especially where the claimant did not suffer any physical injury or was not directly involved in the accident. This article reflects on The Bahamas’ approach to nervous shock, the correlation of “time and space,” where the claimant is said to have witnessed the injury: it will present a discussion of the current understanding of nervous shock and whether it constitutes an appropriate claim.